Remedial Solutions to Improve the Efficiency of Knowledge Based Systems - Kumar Soni, Hemant (International Journal of Computer Sciences and Engineering, 2019)
A learning base is an effectively available information stockpiling center that contains data about a specific item, administration, theme, or idea. Associations make learning bases to house the majority of the information inside their association about a specific subject, to give one area to get to this data. Information bases can target inside representatives (on account of an organization learning base) or the general population - clients or potential clients - who need to study a specific item, subject, or idea. The objective of a learning base is to legitimately give data to these clients, and, on account of an interior framework, to expand the general comprehension of the whole association. Designing and development of a efficient knowledge base system is a challenging task. In this paper author describe the challenges for KBS and failure of KBS and its causes. Author also provide a deep insight the remedial solution to improve the efficiency of a KBS.